Bathwaterism - West, Malcolm (Canadian Journal of Counselling and Psychotherapy, 2012)
The foibles of the fad that is behavior therapy are examined. It is suggested that an SR paradigm is adequate to represent man as a behaving organism. However, the limitation of this model inheres in the fact that man not only behaves, but that he is also a thinking and valuing being. Finally, the implications of an SR conception of man with regard to therapy are discussed.